2014
DOI: 10.1002/hipo.22261
|View full text |Cite
|
Sign up to set email alerts
|

Spatial memory in sedentary and trained diabetic rats: Molecular mechanisms

Abstract: Diabetes mellitus is a chronic disease that has been associated with memory loss, neurological disorders, and Alzheimer's disease. Some studies show the importance of physical exercise to prevent and minimize various neurological disorders. It is believed that the positive effects of exercise on brain functions are mediated by brain insulin and insulin-like growth factor-1 (IGF-1) signaling. In this study, we investigate the role of swimming exercise training on hippocampus proteins related to insulin/IGF-1 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Inoue et al [23] reported rats that ran on the treadmill for 60 min/day, 5 times a week over 6 weeks exhibited higher spatial memory performance than sedentary rats when tested in the Morris Water Maze 24 hours after memory training. Swimming exercise has been related to the retention of short-term memory [24][25][26][27][28][29][30]. Diegues et al [24] demonstrated that rats submitted to swimming exercise over 6 weeks showed an improved spatial memory evaluated by the lower escape latency in the retention test when compared to rats of the control group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inoue et al [23] reported rats that ran on the treadmill for 60 min/day, 5 times a week over 6 weeks exhibited higher spatial memory performance than sedentary rats when tested in the Morris Water Maze 24 hours after memory training. Swimming exercise has been related to the retention of short-term memory [24][25][26][27][28][29][30]. Diegues et al [24] demonstrated that rats submitted to swimming exercise over 6 weeks showed an improved spatial memory evaluated by the lower escape latency in the retention test when compared to rats of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Swimming exercise has been related to the retention of short-term memory [24][25][26][27][28][29][30]. Diegues et al [24] demonstrated that rats submitted to swimming exercise over 6 weeks showed an improved spatial memory evaluated by the lower escape latency in the retention test when compared to rats of the control group. In addition, rats submitted to swimming exercise over 8 weeks [25] also showed an improved contextual memory assessed 24 hours after passive avoidance training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these findings indicate that insulin/IGF signaling is impaired in the diabetic brain, and this signaling might have an impact on aging-related brain dysfunction (82). Interestingly, aerobic exercise increases some proteins related to the insulin/IGF-1 pathway in the hippocampus and improves spatial memory in diabetic rats (83). …”
Section: Alzheimer Pathological Feature-independent Mechanismsmentioning
confidence: 99%